KORELASI ANTARA SELF-EFFICACY DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VII SMPN 20 PEKANBARU - Riyanti Riyanti; Darmawati Darmawati; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aims to find the correlation between self-Efficacy and motivation through students’ result of study at the seventh grade of SMPN 20 Pekanbaru. It was conducted on July until August 2020 in SMPN 20 Pekanbaru. This research is a quantitative research with correlational approach. Since there is the pandemic of Covid-19, the data was gathered by using google form and asked the students to give their responds through the statements in the questionnaire of self-efficacy and the questionnaire of motivation. Besides the questionnaire, the data of this research is the result of the students’ test in the biology subject. The finding of this research showed that (1) there is a significant correlation between self-efficacy and the result of the study. (2) there is a significant correlation between motivation and the result of the study, and (3) there is a significant correlation between self-efficacy and motivation through the result of the study. So, based on the finding of this research, it will be better if the students can improve their self-efficacy and their motivation to increase their result of the study.Key Words: Correlation, Self-Efficacy, Motivation, The Result Of The Study